Biochemical Changes Associated with Abortion: A Review - Omogbai, Ohiwerei Wisdom; Eseigbe Emmanuel Ebosetale (MultiTech Publisher, 2024)
Abortion, whether spontaneous or medically induced, triggers a range of physiological and biochemical changes in the female body. The termination of pregnancy influences hormonal balance, metabolism, and enzymatic activity, which can affect reproductive health. This review explores the biochemical impacts of abortion, including hormonal disruptions, oxidative stress, inflammatory responses, immune system alterations, neurotransmitter imbalances, and potential long-term metabolic effects